Corporate Criminal Liability in Corruption in the Procurement of Goods and Services of Construction Sector - Yusuf Fitrohansyah; Appry M. Silaban (Wiraraja University, 2024)
The hope of the Indonesian people in terms of eradicating corruption in the construction sector is not just a solution through political compromise but rather the goal of improving the welfare of the community with the availability of adequate and sustainable national development infrastructure. In Article 1 point e of Law No. 5 of 1999, a business actor is every individual or business entity, whether in the form of a legal entity or a non-legal entity that is established and domiciled or carries out activities, either alone or jointly through an agreement, Organizing various business activities in the economic sector. The research method used is normative juridical research where the legal research method is carried out by researching literature materials or secondary materials. The result is, Law enforcers are free to choose theories and doctrines based on the case they face, which is important to ensnare corporations always pay attention to the principle of geen straf zonder schuld (actus non facit reum nisi mens sir rea) by being guided by existing laws. And Corporations can be held accountable when corruption crimes occur in the procurement of goods and services in the construction sector.